EFEKTIVITAS METODE MNEMONIK TERHADAP DAYA INGAT PADA MATERI PROTISTA DI KELAS X SMA BUDI MURNI 3 MEDAN TAHUN AJARAN 2017/2018 - Susrani Simamora; Hudson Sidabutar; Tonggo Sinaga (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the effectiveness of student biology learning using mnemonic method on protista material in grade X SMA Budi Murni 3 Medan School Year 2017/2018. The population of this study were all students of grade X SMA Budi Murni 3 Medan which amounted to 67 students consisting of two classes namely X A and X B. Sampling in this study was done randomly (random sampling) that is class X A consisting of 32 students. This research is a pre-experiment research. Instruments used to collect data are objective tests in multiple choice that have been tested to try validity, reliability, difficulty and distinguishing power. The instrument used is 25 questions. From the data analysis, students recalled in classical manner that is 70,5%. Based on the results of the data, the effectiveness can be illustrated with individual students' recollections of 15 students having R ≥ 70 (46.87%), 11 students having 60 <R <70 (34.37%) and 6 students having R <60 (18 , 75%). The effectiveness of treatment is not met where t count is greater than ttable that is 15,33> 1,6955 so H1 accepted where there is difference siginfikan between result of posttest and retest. So it can be concluded that the use of methods of mnemonics in protista material in grade X SMA Budi Murni 3 Medan Year Learning 2017/2018 is not effective.Keywords: Mnemonics, Effectiveness, Memory